Incas and Amazonians: Ancestral ethnic antagonism - Kauffmann Doig, Federico (2010)
Although the contacts between the inhabitants of the Inca or Andean area and the Amazon area date back 5,000 years, an asymmetric cultural development is observed in both spaces over the millennia. It is argued that this cultural asymmetry cannot be explained by a greater or lesser intellectual capacity of Andeans or Amazonians, since both descend from branches of the same racial stock, the Paleo-Mongolian. Consequently, the gap in the cultural process must have other roots. These could be due to environmental conditions. Perhaps this factor was the one that marked the cultural disparity that is perceived, if the Andean settlers are compared with the Amazonian. We consider that the aforementioned cultural differences between Amazonians and Andeans are what seem to also explain the presence of ethnic antagonism prevailing between them. There is news of these differences in the chronicles of the 16th and 17th centuries, which allow us to discover their existence already in Inca times. In these sources there are specific mentions of the contempt that, at that time, the Andeans already showed towards the jungle people, whom they despotically called chunchos. This ethnic disdain towards the original Amazonians subsists, veiled or openly, even today, among us.